A review on governance principles of cross-border Central Bank digital currency interoperability: A case study of Project Dunbar - Annathurai, Anusha; Norwazli, Abdul Wahab; Nurul Syafidah, Jamil (Penerbit Universiti Malaysia Pahang, 2024)
Cross-border central bank digital currency (CBDC) interoperability projects involving multiple CBDC (mCBDC) initiatives through collaboration among central banks have increased due to fintech innovation. In response to the governance concerns raised by Project Dunbar, one of the pilot initiatives, this study attempted to assess its compliance with the principles of cross-border Central Bank Digital Currency (CBDC) interoperable governance. Despite the study's reliance on grey literature, the interoperable governance enhancements that Project Dunbar requires were highlighted based on the following principles: (1) transparency and accountability, (2) oversight authorities, (3) user accessibility and inclusion and (4) inter-jurisdictional cooperation. The study proposes further studies on the development of implementation strategies and review of other initiatives as case studies.